Three-Dimensional Segmentation and Reconstruction of Neuronal Nuclei in Confocal Microscopic Images - Ruszczycki, Błażej; Pels, Katarzyna Karolina; Walczak, Agnieszka; Zamłyńska, Katarzyna; Such, Michał; Szczepankiewicz, Andrzej Antoni; Hall, Małgorzata Hanna; Magalska, Adriana; Magnowska, Marta; Wolny, Artur; Bokota, Grzegorz; Basu, Subhadip; et al. (Frontiers in Neuroanatomy, 2019)
The detailed architectural examination of the neuronal nuclei in any brain region, using confocal microscopy, requires quantification of fluorescent signals in three-dimensional stacks of confocal images. An essential prerequisite to any quantification is the segmentation of the nuclei which are typically tightly packed in the tissue, the extreme being the hippocampal dentate gyrus (DG), in which nuclei frequently appear to overlap due to limitations in microscope resolution. Segmentation in DG is a challenging task due to the presence of a significant amount of image artifacts and densely packed nuclei. Accordingly, we established an algorithm based on continuous boundary tracing criterion aiming to reconstruct the nucleus surface and to separate the adjacent nuclei. The presented algorithm neither uses a pre-built nucleus model, nor performs image thresholding, which makes it robust against variations in image intensity and poor contrast. Further, the reconstructed surface is used to study morphology and spatial arrangement of the nuclear interior. The presented method is generally dedicated to segmentation of crowded, overlapping objects in 3D space. In particular, it allows us to study quantitatively the architecture of the neuronal nucleus using confocal-microscopic approach.